The automatic assessment of Z specifications - Shukur, Zarina (1999)
The need to automate the process of assessing a specification in a learning environment is identified to be one of the fundamental ways to improve the use of formal notation in specifying a real system. General issues involved in building an automatic marking system for computer-based courses are explored. Techniques that have been proposed for assessing a specification are also discussed. By considering the issues and the techniques, we describe how they can be used to build a system that is able to give a quality grade to a specification that is written in the Z language. In the system, four quality factors are taken into consideration; maintainability of a specification (which considers the typographic arrangement of a specification and the specification complexity), and correctness of a specification (which reflects the static correctness and the dynamic correctness of a specification). By using suitable quality metrics for specification maintainability, the results that are produced are compared to some values which can either be absolute values or relative to the model answer. The marks awarded for this factor are based on this comparison. Static correctness is carried out by applying a syntax and type checker. The marks granted for this factor depend on the outcome of the checker. Dynamic correctness is determined by employing a testing technique. In the context of a specification, the behaviour of a system-state, which is represented by so-called state variables, is analysed. The specification is 'executed' by using animation. The marks are given according to the correctness of the output and the final state. The system is implemented within the well-known courseware management system, Ceilidh. There are fundamental differences between Z specifications, and the subject matter of other courses taught using the Ceilidh system (which are mostly computer programming courses). For this reason we take some time in this thesis to explain (in some detail) the incorporation of the system within Ceilidh. The need for the fundamental components (i.e the editor, the syntax and type checker, the animator and the automatic marker) are discussed and described. The system has been used by a group of 13 students who attended a Z course within the School of Computer Science and Information Technology at the University of Nottingham during the 1997-1998 academic year. The students were given a questionnaire about the system. An analysis of these questionnaires shows that the currently implemented tools are beneficial and helpful to the students. We also test the results of the system and compare them with a small selected group of human markers. The testing reveals very encouraging results and shows that the system can mark student scripts with a good degree of accuracy. We conclude that this system can provide a very useful aid for teachers of the Z Specification language.